Electronic optimization for an energy harvesting system based on magnetoelectric Metglas/poly(vinylidene fluoride)/Metglas composites. (19th July 2016) - Reis, S; Silva, M P; Castro, N; Correia, V; Rocha, J G; Martins, P; Lasheras, A; Gutierrez, J; Lanceros-Mendez, S
Abstract: Harvesting magnetic energy from the environment is becoming increasingly attractive for being a renewable and inexhaustible power source, ubiquitous and accessible in remote locations. In particular, magnetic harvesting with polymer-based magnetoelectric (ME) materials meet the industry demands of being flexible, showing large area potential, lightweight and biocompatibility. In order to get the best energy harvesting process, the extraction circuit needs to be optimized in order to be useful for powering devices. This paper discusses the design and performance of five interface circuits, a full-wave bridge rectifier, two Cockcroft–Walton voltage multipliers (with 1 and 2 stages) and two Dickson voltage multipliers (with 2 and 3 stages), for the energy harvesting from a Fe61.6 Co16.4 Si10.8 B11.2 (Metglas)/polyvinylidene fluoride/Metglas ME composite. Maximum power and power density values of 12 μ W and 0.9 mW cm −3 were obtained, respectively, with the Dickson voltage multiplier with two stages, for a load resistance of 180 kΩ, at 7 Oe DC magnetic field and a 54.5 kHz resonance frequency. Such performance is useful for microdevice applications in hard-to-reach locations and for traditional devices such as electric windows, door locking, and tire pressure monitoring.